2021
DOI: 10.20473/jmtt.v14i1.24183
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Relationship among E-Learning Platforms, Technical System Quality and Perceived Students’ Satisfaction on Higher Educations’ System for E-Learning

Abstract: Currently, most Indonesian universities have adopted an online academic management information system (AMIS) to provide academic and administrative service activities. This study aims to explore the relationship between the e-learning platforms and the technical system quality, and the perceived satisfaction of students. Data were collected using questionnaires distributed to 286 students of a university. The questionnaire showed that there is a difference in the e-learning tools, techniques, or platforms used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
3
0
1
Order By: Relevance
“…As shown in Table 9, the minimum and maximum total SP scores matched theoretical values. However, the mean total SP score was 16.25, which is much higher than the theoretical average SP score (12). This indicated that the mean level of agreement with the SP items was high.…”
Section: Service Quality Scoresmentioning
confidence: 71%
See 2 more Smart Citations
“…As shown in Table 9, the minimum and maximum total SP scores matched theoretical values. However, the mean total SP score was 16.25, which is much higher than the theoretical average SP score (12). This indicated that the mean level of agreement with the SP items was high.…”
Section: Service Quality Scoresmentioning
confidence: 71%
“…The actual total FEES minimum and maximum scores (4 and 20, respectively (Table 9)) are in agreement with the theoretical values. However, the actual mean FEES total score is 13.99 (Table 9), which is somehow higher than the theoretical average score (12), suggesting that the overall level of agreement of the sample students with the FEES items is around average. In addition, the FEES total scores had an SD value of 3.199 (Table 9), which was high (far from 0), suggesting broad variations among the sample members in the levels of agreement on items of the FEES construct.…”
Section: Service Quality Scoresmentioning
confidence: 73%
See 1 more Smart Citation
“…18 Metode Learning Cell adalah pendekatan pendidikan yang berpusat pada siswa yang menekankan pembelajaran aktif, berpikir kritis, dan kolaborasi. 21 Hal ini dirancang untuk membantu siswa mengembangkan pemahaman mendalam tentang materi pelajaran dan menerapkan pengetahuan mereka dalam situasi dunia nyata. 22 Metode ini melibatkan komponen-komponen utama berikut: 1) Pembelajaran Aktif.…”
Section: Pembahasanunclassified